Relative bibliometrics of intellectual capital and knowledge management in SCOPUS - Aitouche Samia (Proceedings of the International Conference on Industrial Engineering and Operations Management Paris, France, 2018)
The purpose of this work is a bibliometric analysis of the evolution of knowledge management (KM) and intellectual capital (IC) as scientific fields in time. The used data was all articles having “intellectual capital” or “knowledge management” in their title from SCOPUS database exported in Excel and R language is used to compute the indexes. The analysis is using the indexes (H index, N index, G index, I index, lotka’s law), which are most related to references and citations of the articles. We find that KM and IC fields are heterogeneous in cases and homogeneous in other cases vis à vis the applied indexes. This analysis is usefull to researchers in the two areas to find the pionners and the most productive authors to potentially collaborate with them and, the most read articles to use them in literature review. In databases of researches, only H index is offered but to all articles of area defined by the database and not for a set of requested articles. This paper is filling this gap, as the first study of KM and IC using relative bibliometric indexes.